How do impulsive marine seismic surveys impact marine fauna and how can we reduce such impacts? - McCauley, Robert; Duncan, Alec (2017)
A summary of how petroleum seismic survey sources may impact marine fauna from invertebrates to fish, is presented, along with a discussion of the need for developing and testing alternative seismic sources to reduce biological impacts.